Resistance Against Inequality: A Feminist Perspective of Shahraz’s “Zemindar’s Wife” and “Malay Host” - Sabahat Rafique (University of Chitral Journal of Linguistics and Literature, 2024)
In Pakistani fiction, when we try to apply a feminist approach, we realize that female writers reveal the deplorable and pathetic condition of women and their status as second-class citizens who are systematically discriminated against and looked down upon. They explain through fiction the place of women, their struggling existence against the dominating patriarchal mindset. The study also reveals how cultural norms treat them as a minority, devoid of basic rights and freedom. The study will focus on the place of women and their efforts against the cultural norms set by society for centuries. The role of the culture is to let patriarchy oppress women to the utmost level. The present study aims to read two short stories from the book, A Pair of Jeans, by Shahraz, a diaspora Pakistani writer. The main characters of these stories are women. In one story, Malay Host is about facing oppression and androcentrism, which appears as rigid and cruel, while in the second story Zemindar ‘s Wife, a new phase of patriarchy is shown, facing challenge and threat of being supreme and unable to accept change in the set structure. At the end on the basis of the conclusion drawn from the study, the research reveals that short stories support feminism and produce female characters who react against the subjugation of women as a result of the unbending and inflexible framework of patriarchy.